Exploring accessibility, user experience and engagement of digital media among older patients with depression: a pilot and observational screening study protocol of the DiGA4Aged study - Anna Mai; Jan Dieris-Hirche; Magdalena Pape; Nina Timmesfeld; Theresa Sophie Busse; Chantal Giehl; Ina Carola Otte; Horst Christian Vollmar; Georg Juckel; Magdalini Chatsatrian; Jennifer Bosompem; Peter Rasche; et al. (BMJ Open)
Introduction The prevalence of mental health problems is increasing worldwide, particularly in the vulnerable group of older people. The limited availability of therapists, long wait periods and increasing shortage of healthcare resources limit adequate care. As a result, digital applications are becoming more commonplace as an alternative to human therapists. However, these tend to be used by younger people with higher education, digital health literacy and experience. In Germany, applications that are approved by the health authorities, so-called digital health applications (DiGAs), can be prescribed by physicians and psychotherapists. It remains unclear to the extent older people are experienced with, are willing and can use a DiGA. Therefore, this research aims to identify specific challenges of older people’s accessibility, user experience and engagement with DiGA for depressive disorders. The DiGA4Aged project consists of: (1) a pilot study on usability, (2) a screening study on potential participants for a randomised controlled trial (RCT) evaluating the digital experience of the target population and (3) an RCT to test the effectiveness of a digital nurse as individualised user support in the intervention group. This paper focuses on the pilot study and the screening study.Methods and analysis The instrumental components in preparing for the RCT are a mixed-method pilot and observational quantitative screening study, which are described in this manuscript. The pilot study includes questionnaires (covering sociodemographic data, user experience, health literacy, electronic health literacy, media affinity, severity of depression and perceived usability of DiGA), a concurrent think aloud method and a semistructured interview to evaluate two applications with regard to their usability for, acceptance by and needs of older people. The observational screening study collects data of older patients consecutively admitted to an acute care geriatric hospital ward using various questionnaires to identify which clinical and medical factors are associated with the access to, experience with and (non-)use of digital media. Data from the comprehensive geriatric assessment is collected as well as data on their digital media experience and digital health literacy.Ethics and dissemination The overall project DiGA4Aged received ethical approval on 17 November 2023 from the ethics committee of the Medical Faculty of Ruhr-University Bochum (registration number 23-7901). Results will be disseminated within the scientific community via publication in peer-reviewed journals as well as presentation at national conferences. The findings from the pilot study and the observational screening study will determine the selection of the DiGA and the recruitment strategy for the subsequent RCT.Trial registration numbers The pilot study has been prospectively registered in the German Clinical Trials Register (DRKS00033640, registered on 18 March 2024, available from https://drks.de/search/de/trial/DRKS00033640). Likewise, the observational screening study has been prospectively registered in the German Clinical Trials Register (DRKS00032931, registered on 29 November 2023, available from https://drks.de/search/de/trial/DRKS00032931).